Synthesis of water-repellent coating for polyester fabric - Nur Nabilah, Mohd Za’im; Hartina, Mohd Yusop; Wan Norfazilah, Wan Ismail (Ital Publication, 2021)
A new hydrophobic hexyltrimethoxysilane (HTMS) coating for polyester fabric was successfully synthesized via a one-step water-based sol-gel method under acidic condition. Five different molar ratios of HTMS: water (1;40, 1:30, 1:20, 1:12 and 1:3) were prepared and the solution was deposited onto the polyester fabric by a simple dip-pad-cure process. The effect of water content on hydrophobicity was evaluated by manual testing on the treated polyester fabric samples. The effectiveness of hydrophobicity properties was further characterized using water contact angle (WCA) measurement. The optimized molar ratio of 1:3 was found to obtain the best hydrophobic property of 136.2° with particle size 115.3 µm measured using Particle Size Analyzer (PSA). Fourier transform infrared spectroscopy (FTIR) analysis confirmed the success of sol gel process with the presence of Si-O-Si band, which was also determined using energy dispersive X-ray spectroscopy (EDX). The Scanning Electron Microscopy (SEM) images revealed a good surface morphology of the homogenous thin xerogel coating with no visible cracks. Using HTMS without combinations of other precursors resulted in rough surface structure due to the low surface energy caused by long-chain alkyl silane in the HTMS coating and this provided the treated polyester fabric with good hydrophobicity.